Competitividade e orientação para o mercado no arranjo produtivo local embrionário do vestuário de Londrina - Galão, Fabiano Palhares (2006)
This research analyzes the impact of the market orientation and innovation about the performance of the companies of the local embryonic productive arrangement of clothing in Londrina. It identifies the rank of market orientation through Markor scale, elaborated by Kohli, Jaworski and Kumar (1993) and the product innovation implementation, processes and organizational innovations, and also to verify the development of innovative activities of the sample companies. The performance of the companies is obtained through subjective measures and the selected variables were invoicing growth, net profit and return of the investment. The methodological procedures involve the revision of the literature that studies the main factors that characterize the productive arrangements, innovation and market orientation. The chosen approach is the survey, involving a sample of 62 companies. To proceed with the data analysis, we use the coefficient of correlation of Pearson and the Clusters Analysis. Main Results: a) the clothing companies in Londrina are highly oriented for the market and are turned to actions to answer the market; b) the small companies present the highest average of market orientation; c) the innovative behavior of the arrangement is low; d) the process of launching new products has been the most innovative practice used by the companies; e) the main reasons that complicate the innovation activities achievement by the arrangement companies are connected to economic factors. Concludes that market orientation and innovation contribute for the invoicing growth and for the return of investment of the clothing industries in Londrina.